Virulence of Mycobacterium avium in mice does not correlate with resistance to nitric oxide - Susana Lousada (2007)
The growth in C57Bl/6 mice of seven distinct Mycobacterium avium strains was not exacerbated by the disruption of the inducible (type 2) nitric oxide synthase regardless of the virulence of the strain. The susceptibility of this panel of M. avium strains to reactive nitrogen intermediates in a cell-free system, namely the exposure to acidified nitrite or to the NO donor NOG 18, showed that there is no correlation between strain virulence and the corresponding minimal bactericidal and minimal inhibitory concentrations for those compounds determined in vitro.